Integration of Agro-Ecological and Groundwater Resources for the Assessment of Crop Suitability Potential Modeling: The Case of Limpopo Province, South Africa - Khudzadzo, Ndwambi; Nesamvuni, Azwihangwisi Edward; Tshikolomo, Khathutshelo Alfred; Mpandeli, Sylvester; Niekerk, Johan Van; Petja, Brilliant M (Asian Journal of Agriculture and Rural Development, 2021)
A comprehensive subtropical fruit potential model (IUM) was established through novel integration of groundwater resources with multi-criterion predictive parameters. Equal-weights overlay was applied to reclassified and ranked rasters to institute IUM. Avocado and litchi had the least spatial extent that concealed the micro-climatic zones of high rainfall (>1000 mmpa) in Vhembe, Mopane, and Waterberg districts; meanwhile, mango and citrus were the crops with the most extensive province-wide distribution. Subsequent potential was apportioned in these sequences by constituency: Waterberg (1719019 ha), Mopane (977741 ha), Vhembe (764044 ha), Capricorn (579506 ha), and Sekhukhune (379968 ha). The IUM resulted in the demarcation of 8.7 million ha to produce the selected crops, which reflected an increase of 7.7 million from the rainfed suitability model. The integrated model would result in the creation of 10.87 million direct employments. The IUM expanded the agrarian sector with positive spinoffs for agribusiness development.